Province of the Massachusetts-Bay in New-England. By the Honorable, William Stoughton Esq. Lieutenant governour and commander in chief. A proclamation : Whereas the ship Adventure of London ... Given at the Council chamber in Boston, the first day of April 1699 (Printed by Bartholomew Green and John Allen, printers to the governour & Council, 1699)
April 1, 1699 Proclamation by Acting Governor William Stoughton naming Joseph Bradish and various other men for piracy and felony against the ship Adventure of London, commanded by Thomas Gulleck, and issuing arrest warrants for them and anyone who assisted them.